The Relationship between Modified Cash Conversion Cycle & Firms’ Profitability (KASBIT Business Journal, 2019)
The paper aims to study the influence of modified cash; conversion cycle (mCCC) on the earnings of the; companies; in three different sectors of Pakistan includes Automobile, Pharmaceutical and Cement industry. The study uses a panel data from 2009 to 2018 by employing a panel regression model to analyze data covering fourteen registered companies operating in three different industries. The main findings provide empirical pieces of facts that mCCC considerably affects profitability. Moreover, the, firm-level control variables, size, significantly affects, firm profitability while debt ratio and growth are an insignificant impact. Findings suggest that efficient working capital policy enhances firm’s performance. Profitability can be improved by plummeting mCCC as an improved working capital policy positively affects the firm’s value. These practical implications can add value to the existing knowledge of working, capital management through the application of panel regression technique to the panel data of three different industries in Pakistan to introduce the concept of the modified cash; conversion cycle.
Keywords: Modified; cash conversion; cycle; firm size; Firm growth ratio; earning per share; liquidity; debt ratio; panel regression